Crop residue and potassium management strategies to improve water use and soil microbial activities under zero till maize (Zea mays)-wheat (Triticum aestivum) cropping system - M, RAGHAVENDRA; SINGH, Y V; MEENA, M C; DAS, T K; GAIND, S; VERMA, R K (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted with maize-wheat system during 2014-15 and 2015-16 at ICAR-IARI, New Delhi to study the soil microbial activities, crop growth, water use and its related parameters of maize and wheat as influenced by crop residue (CR) and potassium (K) management practices under zero till maize (Zea mays L.)-wheat (Triticum aestivum L.) system. The experiment was laid out in split-plot design with four CR levels (0, 2, 4 and 6 t/ ha) and five K levels (0, 50%, 100%, 150% RDK [recommended dose of K] and 50% RDK + potassium solubilizing bacteria, KSB). The results revealed that significantly higher biomass production, water use efficiency (WUE), irrigation water productivity (IWP) and total water productivity (TWP) of maize and wheat were found with 4.0-6.0 t/ha CR as compared to no CR and 2.0 t/ha CR.This was in consonance with improvement in soil microbial activities. Among K management, 50% RDK+KSB, 100% RDK and 150% RDK were found significantly superior over no K and 50% RDK for soil microbial activities, biomass production, WUE, IWP and TWP of maize and wheat. Thus, a combination of 4.0-6.0 t/ha CR retention and 50% RDK along with seed inoculation of KSB microbial strain could be pre-eminent options to improve crop growth, water use efficiency and soil microbial activities in zero till maize-wheat system.